2018
DOI: 10.1080/23802359.2018.1535840
|View full text |Cite
|
Sign up to set email alerts
|

Complete chloroplast genome sequence of the Pseudostellaria longipedicellata S. Lee, K. Heo & S. C. Kim (Caryophyllaceae)

Abstract: Pseudostellaria longipedicellata which belongs to Caryophyllaceae is endemic in South Korea. In this study, we presented first complete chloroplast genome of P. longipedicellata which is 149,626 bp and has four sub-regions: 81,292 bp of large single copy (LSC) and 16,984 bp of small single copy (SSC) regions are separated by 25,675 bp of inverted repeat (IRs) regions including 126 genes (81 CDS, eight rRNAs, and 37 tRNAs). The overall GC contents of the chloroplast genome were 36.5% and in the LSC, SSC and IR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
41
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 6 publications
3
41
0
1
Order By: Relevance
“…Korea. [23] The major components present in E. cava are phlorotannins and flucoidans which posses various biological properties. Phlorotannins are unique polyphenolic compounds which are produced by the polymerization of phloroglucinol.…”
Section: Discussionmentioning
confidence: 99%
“…Korea. [23] The major components present in E. cava are phlorotannins and flucoidans which posses various biological properties. Phlorotannins are unique polyphenolic compounds which are produced by the polymerization of phloroglucinol.…”
Section: Discussionmentioning
confidence: 99%
“…In the third crosslinking technology, Kim and Lee et al synthesized crosslinked proton exchange membrane by incorporation of sulfonated SPAES into crosslinked network prepared, in situ, from vinyl phosphonic acid (VPA) and diethylene glycol dimethacrylate (DEGDMA) by thermal initiated radical polymerization [38]. The PVPA segments in the crosslinked network improved the high temperature proton conductivity at low humidity with a maximum proton conductivity of 1.0 S m -1 at 120°C and 40% RH.…”
Section: Crosslinked Networkmentioning
confidence: 99%
“…[41][42][43] Alginic acid, a linear copolymer of β-d-mannuronate and α-l-guluronate, is the most abundant polysaccharide in the brown algae, and has widely and intensively been used for bioencapsulation of various cell types including pancreatic islets, mammalian cells, and microbes. [44][45][46] Its facile fabrication capacity for sophisticated microstructures has recently led to the development of alginate hydrogel-based, 3D astrocyte culture platform. [30] Based on the wide use of alginate hydrogels in bioencapsulation, we first attempted to encapsulate astrocytes in the alginate hydrogels, but found that the cell viability was extremely low, presumably because of the lack of the adhesion sites in the pure alginate hydrogel fibers.…”
mentioning
confidence: 99%